Craqueamento catalítico de 1,3,5-triisopropilbenzeno sobre catalisadores micro-mesoporosos visando a produção de hidrocarbonetos leves - Lima, Elys Rayssa Neres (2017)
Some challenges to the domain of catalytic cracking of heavy oil fractions include the development of catalysts with better accessibility to larger molecules in their porous system, in addition to the presence of centers that are resistant to deactivation and allow an operation in short contact times, thus improving yields on high added value products. Micromesoporous catalysts are an important class of new materials that have ample potential in this regard, due to the combination of microporous zeolite and mesoporous materials. In this work, they were developed through hydrothermal synthesis and mechanized series of catalysts of type HY/MCM-48. The catalysts were characterized by X-ray diffraction (XRD) and adsorption and desorption of N2 at 77 K. An influence of different proportions of micro and mesopores on the catalytic cracking reaction of the 1,3,5-triisopropylbenzene (1,3,5-TIPB) molecule was studied, aiming at the production of light hydrocarbons, the degree of deactivation of the catalysts Investigated through elemental analysis of carbon, hydrogen and nitrogen (CHN). The results obtained by the X-ray diffractograms of the synthesized catalysts show characteristic peaks related to the microporous material, the zeolite HY, and the mesoporous material, the MCM-48. The composite catalyst containing 75% zeolite HY and 25% MCM-48 showed adsorption isotherm and N2 desorption characteristic of type I, being the profile of the isotherms was varying according to the composition between micro and mesopores until reaching the type IV in the catalysts with 25% and 50% zeolite. The catalysts developed also have specific surface areas, pore diameters, pore volumes and silica wall thickness in the range of 1098 to 1996 m2 g -1, 3,30 to 3,34 nm, 0,25 to 0,78 cm3 g - 1 and 0,55 to 0,77 nm, respectively. As analyzes of CHN showed that the composites with higher catalytic activity showed a trend towards greater deposition of coke. From the catalytic cracking tests of 1,3,5-TIPB, it can be observed that the main products formed were propene, benzene, isopropylbenzene, 1,3-diisopropylbenzene, 1,4-diisopropylbenzene and coke. The results showed that the catalyst with the highest zeolite content was the most promising in the conversion of 1,3,5-TIPB with high benzene production.